The association of HALP score with low muscle mass in older adults - Liu, Suxia; Huang, Jiansheng; Hu, Xiaolei; Chen, Shuaiqing; Lin, Mingshen (Frontiers in Nutrition, 2025)
BackgroundThe HALP score, combining hemoglobin, albumin, lymphocyte, and platelet parameters, serves as a comprehensive indicator reflecting both inflammatory processes and nutritional conditions. Our investigation aimed to explore the association of this composite score with the prevalence of low muscle mass and associated mortality in the elderly American population.MethodsThe investigation incorporated information from 3,550 individuals aged ≥60 years enrolled in the National Health and Nutrition Examination Survey (NHANES) between 1999 and 2004. Multivariate logistic regression models were employed to assess the presence of low muscle mass, while Cox proportional hazards models examined mortality outcomes. Non-linear associations and inflection points were examined through the application of restricted cubic spline (RCS) methodology. Additional statistical analyses included Kaplan–Meier survival curve, subgroup analyses, interaction testing, and sensitivity analyses.ResultsParticipants within the top ln HALP quartile demonstrated a 29% lower probability of having low muscle mass relative to those in the bottom quartile (OR = 0.71, 95% CI: 0.56, 0.89). Participants with low muscle mass in the top quartile of ln HALP had a 23% reduced risk of all-cause mortality compared to those in the bottom quartile (HR = 0.77, 95% CI: 0.62, 0.97). Non-linear modeling using restricted cubic splines established a critical value at ln HALP = 3.9. Below this value, increasing ln HALP was inversely related to both the presence of low muscle mass (OR = 0.56, 95% CI: 0.41, 0.75) and mortality (HR = 0.53, 95% CI: 0.41, 0.68). No meaningful statistical trends were detected beyond this critical value. Population stratification analyses supported the generalizability of these findings across diverse subgroups (all P for interaction > 0.05).ConclusionThe HALP score demonstrated a negative correlation with the prevalence of low muscle mass and its associated mortality, indicating its utility as a combined indicator for risk assessment.